HUBUNGAN SELF-EFFICACY DENGAN PERILAKU INOVASI DALAM MENGOLAH SAMPAH MENJADI MEDIA BELAJAR DI SLB KABUPATEN X - Alfiyah, Nur; Shinta, Arundati; Lekahena, Femmy (Fakultas Psikologi Universitas Tarumanagara, 2025)
Waste management is a shared responsibility, including for teachers in Special Schools (SLB). Teachers play an important role in fostering students’ environmental awareness, one of which is through recycling waste into creative and educational learning media. However, many teachers are still unable to carry out this effort optimally in their daily teaching and learning activities at school. One factor that may influence this ability is self-efficacy, defined as a person’s belief in their own capacity to perform specific actions. This study aims to empirically examine the relationship between self-efficacy and innovative behavior among SLB teachers in processing waste into learning materials. A total of 68 out of 99 teachers from six SLB schools in District X participated as research samples. Data were collected using two psychological scales, namely the Self-Efficacy Scale and the Innovative Behavior Scale, and analyzed using the Pearson Product-Moment correlation test. The results show a significant positive correlation between self-efficacy and innovative behavior (r = 0.353; p < 0.01). This indicates that the higher the teacher’s self-efficacy, the greater their tendency to behave innovatively in developing school learning activities. Self-efficacy contributed 12.46% to innovative behavior, while the remaining 87.54% was influenced by other factors. Additional tests revealed no gender differences, but significant differences based on years of service.